Digitalized Tourism Practices of Selected Entrepreneurial Hotels in the Philippines Towards a Safe Travel Experience - Jefferson S Marcelo (Journal of Social Entrepreneurship Theory and Practice, 2023)
The development and use of digital technologies are fundamentally altering how people live, work, travel, and conduct business, and they are also reshaping and revolutionizing the tourism industry. This study aimed to assess the digitalized footprint practices of selected hotels in the Philippines towards the implementation of a safe travel experience among prospective and regular tourists in the city and country. Moreover, it sought to determine whether there is a significant relationship between the perceived digitalized tourism experience and the commonness of availing services in the selected establishment in implementing a safe travel experience. The researchers used the Quantitative method to quantify data and generalize results from a sample of a target population. It involved one hundred (100) respondents consisting of customers and employees of the selected hotels in Taguig City. Convenience Sampling was used on this research; therefore, participants were chosen based on their availability and willingness to participate. The statistical test that was used in this research is Pearson Correlation Coefficient. This test was designed to determine the relationship or association between an independent variable (categorical data – Frequency of availing services in the establishment) and dependent variable/s (3 digitalized tourism experiences). Based on the result, it is concluded that there is a significant relationship between the respondents’ perceived digitalized tourism experience and the commonness of availing services in the selected establishment in implementing safe travel experience.